2007
DOI: 10.1111/j.1600-0722.2007.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of dental services among adults in Denmark 1994–2003

Abstract: The purpose of the present study was to measure the consumption of dental services among adults in Denmark and to analyze at what level socio-demographic/socio-economic factors influence dental attendance and oral examinations. A sample of 10% of the total population of 18 yr or older was randomly drawn from a population register, based on a cross-sectional design. Information on the use of dental services was retrieved from public registers along with data on gender, age-group, regions, ethnicity, education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 22 publications
6
35
2
2
Order By: Relevance
“…Hence, the validity and reliability of the obtained data were satisfactory. Furthermore, the fact that our findings on, for instance, oral health behaviour and xerostomia were in full accordance with findings from previous population studies [27][28][29] was comforting and indicated that the present data-sets were usable and trustworthy for their purpose.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the validity and reliability of the obtained data were satisfactory. Furthermore, the fact that our findings on, for instance, oral health behaviour and xerostomia were in full accordance with findings from previous population studies [27][28][29] was comforting and indicated that the present data-sets were usable and trustworthy for their purpose.…”
Section: Discussionsupporting
confidence: 93%
“…The response to each item is scored 0 or 1 with a maximum score of 20. Those scoring 7 or more were classified as having symptoms of mental distress [18].…”
Section: Operational Definitionsmentioning
confidence: 99%
“…Studies from several countries show that migrants utilize dental check-ups less frequently than the respective autochthonous populations [1821]. In Germany, research on the utilization of dental prevention measures among migrants is scarce, especially for adults.…”
Section: Introductionmentioning
confidence: 99%